Expression of miR-451a in Prostate Cancer and Its Effect on Prognosis - Bo Fan; Xiaohua Jin; Qi Ding; Cheng Cao; Yi Shi; Hailiang Zhu; Wenjun Zhou (Tehran University of Medical Sciences, 2021)
Background: To investigate the expression of miR-451a in prostate cancer tissues and its effect on prognosis. Methods: Each of 78 specimens of prostate cancer tissues and corresponding adjacent normal tissues were collected from patients in Changshu Hospital Affiliated to Soochow University, Changshu, China from Apr 2014 to Jun 2015. Real-time quantitative RT-PCR (qRT-PCR) was used to detect the expression of miR-451a in tissues. The relationship between the expression of miR-451a and clinical pathological parameters was analyzed. The median expression of miR-451a in the experimental group was used to distinguish the high and low expressions of miR-451a in the experimental group. Kaplan-Meier was used to analyze the survival of miR-451a high and low expression groups. Results: The expressions of miR-451a in the patient's tissues and serum were decreased, and the correlation analysis found that they were positively correlated. ROC curve analysis showed that miR-451a had a high clinical value in the diagnosis of prostate cancer and the area under the curve was 0.921. The incidence of stage III+IV lymph node metastasis, Gleason score of >7 points and a serum Prostate-specific antigen (PSA) level of >20 ng/ml in patients of the low expression group increased significantly. The 5-yr survival rate of patients with low expression was significantly lower than that of those with high expression (P=0.005). MiR-451a was an independent factor affecting the prognosis of patients. Conclusion: miR-451a is lowly expressed in prostate cancer, and patients with low expression have a poor prognosis.